Comparative retrospective analysis of patients with idiopathic normal pressure hydrocephalus and aqueductal web-related aqueductal stenosis. - Türkkan, Alper; Eser Ocak, Pınar; Altunyuva, Oğuz; Sönmez, Buket; Özpar, Rifat; Bekar, Ahmet (The European Research Journal, 2023)
Objectives: Aquaductal web (AW) is a special form of aqueductal stenosis with similar clinical presentation with idiopathic normal pressure hydrocephalus (iNPH). iNPH is indeed a communicating hydrocephalus syndrome whereas AW is a noncommunicating subtype. Here, we aimed to investigate the similarities and differences between these two different chronic hydrocephalus syndromes in terms of clinical signs and symptoms, response to shunt treatment and postoperative complications. Methods: Forty-one patients who underwent shunt operation with the diagnosis of iNPH or AW at our clinic between January 2010-May 2019 were retrospectively analyzed. Patients were evaluated by age, gender, clinical sign and symptoms, comorbidities, intraoperative and postoperative complications, and early and late postoperative outpatient follow-up findings. Results: Twenty-six patients were classified as iNPH group and 15 patients as AW group. Patients in the AW group were significantly younger (45.5 ± 15.6 years vs. 60.3 ± 15.4 years) than the iNPH group (p = 0.006). There was no statistical difference between the groups in terms of subdural effusion formation, need for shunt revision (p = 1.000). Chronic hydrocephalus symptoms regressed in 23 (88.5%) patients in the NPH group, and at least one of them improved. symptoms. This rate was 66.7% (n = 10) in the AW group. Both groups showed similar clinical improvement with VPS (p = 0.1169). Conclusions: The placement of ventriculoperitoenal shunt is widely used in the treatment of iNPH. As iNPH and AW has clinical similarities despite the discrepancies between underlying pathophysiological mechanisms and both clinical entities respond similarly to shunt treatment we advocate VPS surgery in the management of AW as well.